Measures to Enforce Law Regarding Stay Permit Violation Against Immigration Law Policy - Rojak, Jeje Abdul (Prodi Hukum Tata Negara Fakultas Syariah dan Hukum UIN Sunan Ampel Surabaya, 2022)
Law enforcement and stay permit violation are equally important in immigration law policy in many countries. This article seeks to analyse measures taken by the government to enforce the law to control immigration and the likelihood of stay permit violation within the policy of immigration law. Governments in other countries also take stringent measures to enforce immigration law, involving the arrest and deportation of those who fail to comply with immigration law. However, taking these measures may lead to ultra vires tendencies among immigration officials, human rights violations, and inequality in the system of immigration law, while stay permit violation has been an escalating issue, involving document forgery, overstaying visa, or immigration status misuse for illegal purposes. Tackling this issue should take into account supervision improvement, policy change, and sanction imposition on violators. This study also discusses the essence of maintaining the balance between strict immigration law enforcers and individual rights in immigration. All these measures necessitate transparency in the legal process of immigration, fair access to court, and protection of human rights for all, including immigrants. To face these problems, many countries work along with international organisations and humanitarian agencies to seek better solutions and enforce immigration law while safeguarding individual rights. Further studies are needed to help better understand the impacts of immigration policies on immigrants and to find out how law enforcement can be made more efficient without disrespecting human rights. Keywords: immigration, legal policy, law enforcement